Perizinan Berusaha Berbasis Risiko pada Sektor Perindustrian Pasca Terbitnya Undang-Undang tentang Cipta Kerja: Hal-Hal yang Perlu Diperhatikan - Herlambang, Bonifacius (UNES Law Review, 2024)
Following the issuance of Government Regulation Number 5 of 2021 concerning Risk-Based Business Licensing, Indonesia has adopted a new concept of business licensing based on risk levels. This concept aims to facilitate business operations for entrepreneurs. This study focuses on the risk-based licensing mechanism in the industrial sector from the perspectives of the government (as regulator) and industrial business actors. The research aims to analyze the differences in licensing mechanisms before and after the enactment of Law Number 11 of 2020 concerning Job Creation, which was later amended by Law Number 6 of 2023, and to identify key aspects to be considered in the implementation of risk-based business licensing. The method used is doctrinal research involving the analysis of legal doctrines, development, and regulatory implementation mechanisms. The findings indicate that risk-based licensing classifies business permits into four risk levels: low, medium-low, medium-high, and high. Critical aspects of this mechanism's implementation include the issuance of Government Regulation in Lieu of Law Number 2 of 2022, the concept of industrial activity supervision and control, and the relation of PP 5/2021 to legal principles and theories. The study concludes that the risk-based licensing concept aligns with the principles of justice, utility, and legal certainty.